TEACHING LISTENING AMONG BANGLADESHI LEARNERS: A CASE STUDY ON TEACHERS’ EFFECTIVE FEEDBACK AND STUDENTS’ SITUATIONAL IMPRESSIONS - Ahmed, Md. Kawser (American International Journal of Social Science Research, 2021)
Listening centralizes upon the comprehension of messages coupled with pronunciations or sounds from speakers-be they are native or non-native and local or foreigner in the scopes of formal conversation, business talk and classroom lectures in the context of Bangladesh. Bangladeshi learners find listening as a complex and incomprehensible skill of four skills of English language. They often are not able to understand pronunciation patterns and accentual variations used in speeches or conversations. Listening requires systematic strategies in understanding audio or vocal track for which logistic support is highly essential. Managing technical support is at times difficult for teachers and administration because of financial constraints. This study will concentrate on how teachers ensure pedagogical supports and experimental aspects to help learners understand listening effectively with methodological study. This paper will deal with how learners overcome the stages of listening difficulties and comprehend different phonological aspects successfully. In addition, one of the prime concentrations of this paper is to identify impediments of teaching listening, teachers’ inefficiency in listening skill and students’ negligence in achieving mastery on listening.